Orchid Pollination Biology - Haleigh Ray; Wagner Vendrame (EDIS)
Orchids and their pollinators have developed fascinating co-adaptations that promote orchid pollination. This 6-page fact sheet details the various and often strange ways that orchids attract pollinators. The kinds of insects and animals that pollinate orchids and orchids’ reproductive anatomies and processes are also covered. Written by Haleigh Ray and Wagner Vendrame, and published by the UF Department of Environmental Horticulture, June 2015.